Association of a (TTTA)n microsatellite and a TCT del/ins polymorphisms in the aromatase gene (CYP19) with hip fracture risk in Mexican postmenopausal women. (2nd December 2015) - Casas-Avila, Leonora; Valdés-Flores, Margarita; Miranda-Duarte, Antonio; Ponce de León-Suárez, Valeria; Castro-Hernández, Clementina; Rubio-Lightbourn, Julieta; Hidalgo-Bravo, Alberto
Abstract: A (TTTA)n polymorphism in the aromatase gene has been studied in relation to bone mineral density (BMD). The low number of TTTA repeats has been associated with low BMD and fracture risk. The aim of this study was to search for associations of TTTA copy number with hip fracture and lumbar spine osteoporosis in Mexican peri and postmenopausal women. The allele with seven repeats was present in the two reported versions, with or without a TCT deletion upstream of the microsatellite (A1 and A2, respectively). After adjustment by confounders, the A1 allele and the A1A1 genotype were significantly associated with an elevated risk of fracture ( p  = 0.034, OR = 3.2 [95% CI, 1.09–9.41] and p  = 0.019, OR = 2.26 [95% CI, 1.14–4.49], respectively) and the A2 allele was associated with protection of hip fracture ( p  = 0.04, OR = 0.48, [95% CI, 0.22–1.05]) as the A2A2 genotype ( p  = 0.048, OR = 0.29 [95% CI, 0.06–1.16]). The analysis allowed us to defining the usefulness of the (TTTA)n polymorphism in the aromatase gene as an indicator of hip fracture risk in Mexican population.